ISO/IATF16949 a Lean Manufacturing Framework or a Wasteful Process - Kheradnejad, Ali (My University, 2018)
The Quality Management Systems in automotive industry known as ISO/TS16949 which recently has been updated into ISO/IATF16949:2016 developed by western major car manufacturers as an alternative approach for Total Quality Management (TQM). As it is not tailor-made for each of the western OEM's, however by introducing customer specific requirements to the requirements made it more suitable for OEM's to monitor and manage the quality and reliability of the products and processes throughout the supply chain. On the other hand, the lean philosophy is a key for cost reduction and in simple words 'do more with less'. As by some, the processes and the significant costs of certification and maintaining the certification is being considered as wastes, without taking into account the benefits, this study is striving to clarify this picture. The scope of the study is a OEM which I was working in last 18 months and my intention is to demonstrate whether with a serious commitment to IATF QMS the well known lean wastes in manufacturing reduces or not. The two departments including Warranty Claims (For all models) and Maintenance (Assembly and Body-In-White) performance measures reviewed and analysed as they are their performance can indicate wastes and success of lean manufacturing. The results of this study denote a significant improvement in Warranty claims and a considerable improvement in efficiency and effectiveness in Maintenance teams after improvement in QMS.
Keywords: Automotive; Lean Manufacturing; Kaizen; Continual Improvement; Continuous Improvement; Quality Management Systems (QMS); Quality Assurance; ISO/TS 16949:2008; ISO 9001: 2015; IATF 16949:2016; Core Tools; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|